2016
DOI: 10.1111/cup.12693
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial sheath neuroma: evidence supporting a hyperplastic etiology and epidermal origin

Abstract: An epithelial sheath neuroma (ESN) is a rare benign process of unknown pathogenesis, which is characterized histologically by multiple enlarged peripheral nerve fibers ensheathed by mature squamous epithelium. The histologic features can elicit concern for carcinomatous perineural invasion. The process is limited to the superficial dermis and is surrounded by a loose myxoid stroma, lymphocytic infiltrate and sometimes prominent infundibular cysts. The etiology of this peculiar entity has been debated and theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Each case of ESN reported has been described to be cured with shave biopsy or simple excision . We report the first case of ESN to extend down to the subcutis, demonstrating that not all cases of ESN are confined simply to the superficial dermis.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Each case of ESN reported has been described to be cured with shave biopsy or simple excision . We report the first case of ESN to extend down to the subcutis, demonstrating that not all cases of ESN are confined simply to the superficial dermis.…”
Section: Discussionmentioning
confidence: 81%
“…Hirano‐Ali et al described a case in a patient with papular urticaria showing a connection to the epidermis and pointed out that there have been several cases of ESN showing overlying epidermal change consistent with lichen simplex chronicus. Moreover, Vandergriff et al reported a case of multifocal ESN with two papules clinically 1 cm apart with an associated acanthotic epidermis on pathology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations